MEDICINAL PLANTS CULTIVATED IN BAPEDI TRADITIONAL HEALERS HOMEGARDENS, LIMPOPO PROVINCE, SOUTH AFRICA - Semenya, S S; Potgieter, M J (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Plants used for medicinal purposes are very common feature in Bapedi traditional healer’s home-gardens, but information about their diversity and application is not available.Materials and methods: To investigate medicinal plants found in Bapedi healer’s home-gardens, 51 traditional health practitioners were interviewed using a semi-structured questionnaire in 17 municipalities of the Limpopo Province of South Africa, during the first half of 2013.Results: A total of 43 plant species (67.4% indigenous and 32.5% exotics) from 32 families, mostly from the Asteraceae and Apocynaceae (9.3% each) were documented. Species cultivated in home-gardens were used to treat three major groups of ailments that include sexually transmitted infections (44.1%), chronic diseases of life style (44.1%) and reproductive ailments (32.5%). The exotics Catharanthus roseus (54.9%) and Carica papaya (15.6%) was the most cultivated. Threatened (11.6%) and protected (6.9%) species are also present in home-gardens, mostly due to their unavailability in natural areas. Conclusion: This study concludes that the practice of cultivating medicinal plant species in home-gardens is a positive development that in the long term will sustain both species and accompanying indigenous knowledge, as well as preserve the cultural identity of the Bapedi.